Land Tenure Security and Sustainable Land Investment: Evidence from National Plot-Level Data in Rural China - Xiaolong Sun; Jinmin Wang; Fangping Rao (Land)
The linkage between land tenure security and land quality improvement investment is crucial given that the land tenure security system is a widely applied policy tool for the protection of cultivation land in developing countries. Drawing on the triple land tenure security framework, this paper examines the impact of the de jure and the de facto land tenure security on farming households’ decisions about using organic fertilizer on their plots in China, based on a national survey dataset covering 2308 plots matched with 962 farming households across 8 provinces in China (Shangdong, Shangxi, Jilin, Zhejiang, Henan, Gansu, Hunan, and Sichuan) from January to July 2013. The empirical results show that the de facto land tenure security affected the use of organic fertilizer by the farming households positively. In comparison, the impact of the de jure land tenure security on the use of organic fertilizer by farming households was modest. It is suggested that the government should implement the policies effectively to promote de jure land tenure security and encourage farming households to make sustainable land investment.